Are customers still with us? The influence of optimum stimulation level and IT-specific traits on mobile banking discontinuous usage intentions. (March 2019) - Avornyo, Philip; Fang, Jiaming; Antwi, Collins Opoku; Aboagye, Michael Osei; Boadi, Evans Asante
Abstract: Information Systems (IS) and the platforms they provide can be conceived of as a stimulus which engenders customers' reactions. In this respect, banks could benefit from a keen understanding of consumers' individual needs in the context of their personality traits in their efforts to optimize the use of IS for service development and management. In accordance with this, the present study adopted the Trait Hierarchical Model (THM) and the Optimum Stimulation Level Theory (OSLT), to explore (1) the influence of Optimum Stimulation Level (OSL), a broad personality trait that determines individuals' need for stimulation on Mobile Banking Discontinuous Usage Intentions (MBDUI), (2) the mediating effects of stable IT-specific traits – Microcomputer Playfulness (MCP) and Personal Innovativeness in Information System (PIIT) on the OSL – MBDUI relations and (3) the interaction of Perceived Ease of Use (PEOU) on the direct and indirect OSL – MBDUI relation. The findings supported most of the hypothesized paths, buttressing the theoretical underpinnings of the THM as well as the OSLT, and empirically extending the OSL framework. The study further outlines practical measures for m-banking service management and directions for future studies. Highlights: Optimum Stimulation Level (OSL) predicts M-banking Discontinuous Usage Intentions (MBDUI). Personal Innovativeness (PIIT) and Microcomputer Playfulness (MCP) mediate the OSL - MBDUI link. Perceived Ease of Use (PEOU) modifies the OSL-MBDUI link. The indirect effect of PIIT on OSL – MBDUI link is moderated by PEOU.